Emraclidine, a novel positive allosteric modulator of cholinergic M4 receptors, for the treatment of schizophrenia: a two-part, randomised, double-blind, placebo-controlled, phase 1b trial. Issue 10369 (17th December 2022) - Krystal, John H; Kane, John M; Correll, Christoph U; Walling, David P; Leoni, Matthew; Duvvuri, Sridhar; Patel, Shrinal; Chang, Ih; Iredale, Philip; Frohlich, Lillian; Versavel, Stacey; Perry, Pamela; et al.
Summary: Background: Emraclidine is a novel, brain-penetrant, highly selective M4 receptor positive allosteric modulator in development for the treatment of schizophrenia. We aimed to evaluate the safety and tolerability of multiple ascending doses of emraclidine in patients with schizophrenia. Methods: We conducted a two-part, randomised, phase 1b trial in the USA. Eligible participants were aged 18–50 years (part A) or 18–55 years (part B) with a primary diagnosis of schizophrenia per the Diagnostic and Statistical Manual of Mental Disorders 5th edition, as confirmed by the Mini International Neuropsychiatric Interview, and extrapyramidal symptom assessments indicating normal to mild symptoms at screening. Part A evaluated the safety and tolerability of emraclidine in five cohorts of participants with stable schizophrenia who received ascending oral doses of emraclidine 5–40 mg (40 mg was administered as 20 mg twice daily) or placebo at a single US site. Part B was a double-blind, randomised, placebo-controlled study that enrolled adults with acute schizophrenia across five US sites; participants were randomly assigned (1:1:1) to receive emraclidine 30 mg once daily, emraclidine 20 mg twice daily, or placebo for 6 weeks (doses established in part A). The primary endpoint was safety and tolerability, assessed in the safety population (participants who received at least one dose of emraclidine or placebo). This trial is now complete and is registered with ClinicalTrials.gov, NCT04136873 . Findings: Between Sept 23, 2019, and Sept 17, 2020, 118 patients were assessed for eligibility and 49 were randomly assigned across five cohorts in part A. 44 participants completed the study, with 36 participants receiving emraclidine and eight receiving placebo. The two highest doses tested were selected for part B. Between Oct 12, 2020, and May 7, 2021, 148 patients were assessed for eligibility and 81 were randomly assigned to emraclidine 30 mg once daily (n=27), emraclidine 20 mg twice daily (n=27), or placebo (n=27) in part B. Incidence of adverse events (14 [52%] of 27 participants in the emraclidine 30 mg once daily group, 15 [56%] of 27 in the emraclidine 20 mg twice daily group, and 14 [52%] of 27 in the placebo group), clinical assessments, and weight changes were similar across groups. The most common adverse event was headache (15 [28%] of 54 participants in the emraclidine groups, seven [26%] of 27 in the placebo group). Modest, transient increases in blood pressure and heart rate in emraclidine groups observed at treatment initiation diminished over time and were not considered clinically meaningful by week 6. Interpretation: These data support further investigation of emraclidine as a once-daily treatment for schizophrenia without need for titration and with a potentially favourable side-effect profile. Funding: Cerevel Therapeutics.